1985
DOI: 10.1007/bf01570350
|View full text |Cite
|
Sign up to set email alerts
|

Correction of age- and disease-related contour deficiencies of the face

Abstract: The main indications for Zyderm Collagen Implant in the face are for the correction of acne scars and facial wrinkles, such as the lines of the forehead, crow's feet, naso-labial crease lines, and creases of the lips. Few complications have been found, but it is vitally important that patients are carefully assessed and well informed before treatment is commenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…1 Early clinical studies with the injectable bovine collagen Zyderm demonstrated its effectiveness in correcting age-related facial wrinkles, furrows, and other dermal defects. [2][3][4][5][6] However, the temporary nature of the clinical correction 7,8 has prompted the development of more stable biomaterials. Zyplast, a glutaraldehyde cross-linked bovine collagen, allows deeper placement of the implant and provides a more durable aesthetic effect than Zyderm, with maintenance injections being required every 4 to 6 months.…”
Section: Q-med Gave Supplies and Funding For This Researchmentioning
confidence: 99%
“…1 Early clinical studies with the injectable bovine collagen Zyderm demonstrated its effectiveness in correcting age-related facial wrinkles, furrows, and other dermal defects. [2][3][4][5][6] However, the temporary nature of the clinical correction 7,8 has prompted the development of more stable biomaterials. Zyplast, a glutaraldehyde cross-linked bovine collagen, allows deeper placement of the implant and provides a more durable aesthetic effect than Zyderm, with maintenance injections being required every 4 to 6 months.…”
Section: Q-med Gave Supplies and Funding For This Researchmentioning
confidence: 99%
“…Early clinical studies with the injectable bovine collagen Zyderm demonstrated its effectiveness in correcting age-related facial wrinkles and other dermal defects. 2,8,9 However, the short-term nature of this clinical correction has prompted the development of new, more stable products (e.g., Zyplast), and the past decade has seen an explosion in the technology of injectable filler materials for soft-tissue augmentation in the face. Zyplast, a glutaraldehyde crosslinked bovine collagen, allows deeper placement of the implant and provides a more durable aesthetic effect than Zyderm, with maintenance injections being required every 4 to 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Zyplast® is primarily used to treat deeper scar tissue including acne scars and the vermillion border of the lip. [6] Various distinctive studies have demonstrated the efficacy of Zyderm® in the cosmetic industry including a study conducted by Nicolle, [7] which showed the effectiveness of Zyderm® II in 350 patients treated for various facial contour defects including acne, glabellar frown lines, periorbital lines and naso-labial folds. Eighty percent of the patients treated were satisfied with their results although 5 patients showed signs of a positive localized reaction to the test dosage of Zyderm® II.…”
Section: Bovine Collagenmentioning
confidence: 99%
“…Eighty percent of the patients treated were satisfied with their results although 5 patients showed signs of a positive localized reaction to the test dosage of Zyderm® II. [7] Additionally, a clinical The depth of needle insertion ranges from superficial to mid-dermis and is dependent on both wrinkle type and filler type; (ii) release of intradermal fillers through the needle; (iii) filler insertion results in smoothed wrinkles and the effect is long-lasting [31] study by Bailin and Bailin [8] in which 8 patients were treated with Zyplast® and Zyderm® I and II for surgical scars, acne scars and rhytids or a combination of these found that both products were effective. Results lasted between 4-6 months for rhytids and 6-9 months for scars regardless of which product was used.…”
Section: Bovine Collagenmentioning
confidence: 99%